2007
DOI: 10.1167/7.7.10
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the posterior surface to the coma aberration of the human cornea

Abstract: Scheimpflug imaging was used to measure in six meridians the shape of the anterior and posterior cornea of the right eye of 114 subjects, ranging in age from 18 to 65 years. Subsequently, a three-dimensional model of the shape of the whole cornea was reconstructed, from which the coma aberration of the anterior and whole cornea could be calculated. This made it possible to investigate the compensatory role of the posterior surface to the coma aberration of the anterior corneal surface with age. Results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 24 publications
5
47
0
Order By: Relevance
“…In agreement with prior work by Dubbelman et al [45,46] we found that on average the posterior corneal surface compensated part of the irregularities of the anterior cornea, in particular astigmatism (31% [45] / 18% in the current study) and coma (from 3.5% [46] / 12% in the current study). As in the cornea, our study also revealed a high correlation between the magnitude of the irregularities of the anterior and posterior lens surfaces in coma and trefoil terms, indicating coordinated development.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with prior work by Dubbelman et al [45,46] we found that on average the posterior corneal surface compensated part of the irregularities of the anterior cornea, in particular astigmatism (31% [45] / 18% in the current study) and coma (from 3.5% [46] / 12% in the current study). As in the cornea, our study also revealed a high correlation between the magnitude of the irregularities of the anterior and posterior lens surfaces in coma and trefoil terms, indicating coordinated development.…”
Section: Discussionsupporting
confidence: 94%
“…Chen and Yoon 11 found mean compensations of 21% for astigmatism, 6% for coma, and 18% for spherical aberration. Yamaguchi et al 15 wrote that compensation for higher-order aberrations was approximately 10%, Dubbelman et al 12 found approximately 4% compensation for coma, and Sicam et al 13 reported variable compensation of 10% to À26% for spherical aberration. In our study, the mean compensations of the anterior cornea by the posterior cornea were approximately one-third for the major higherorder aberrations of horizontal astigmatism, horizontal coma, and spherical aberrations, and the RMS values of the posterior cornea were also approximately one-third of those of the anterior cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, other studies have found much higher aberrations at the anterior surface than at the posterior surface using different instruments, including, the scanning slit Bausch & Lomb (Houston, TX, USA) Orbscan, 10,11 a laboratory Scheimpflug imager, 12,13 the Pentacam, 14 and anterior segment optical coherence tomography (SS-1000; Tomey, Nagoya, Japan). 15 These studies used different analyses including Fourier decomposition of the surfaces, 10 raytracing through surfaces, 12,13,15 and comparing the surface shapes with ideal (aberration-free) shapes. 11,14 A potential problem with the latter approaches arises if the object for the posterior cornea is set at infinity rather than that corresponding to refraction by the anterior cornea, as the choice of object position affects aberration estimates.…”
mentioning
confidence: 99%
“…139 Using Scheimpflug 3D-reconstruction and ray-tracing in normal eyes, Dubbelman et al found that the posterior cornea compensated for 3.5% of the anterior corneal coma aberration. 32 In a wavefront study of keratoconus eyes, Chen et al found that the posterior cornea compensated for 14-24% of the coma aberration of the anterior cornea. 24 Yamaguchi et al developed a surface parallelism index (SPI) to quantify changes in parallelism, 139 with a lower SPI indicating a greater degree of parallelism between the anterior and posterior corneal surfaces.…”
Section: Accepted Manuscriptmentioning
confidence: 99%